Transcriptomic insights into mycorrhizal interactions with tomato root: a comparative study of short- and long-term post-inoculation responses - Abdelsattar, Mohamed; Soliman, Maali S.; Mohamed, Rasha A.; Radwan, Khaled H.; El-Mahdy, Mohamed M.; Mousa, Khaled H.; Khalil, Shaimaa R. M.; Osman, Engy; Alameldin, Hussien F.; Hussein, Ahmed; Hassanein, Sameh E.; Abdallah, Naglaa A.; et al. (Frontiers in Genetics, 2024)
Background Arbuscular mycorrhiza (AM) refers to a symbiotic association between plant roots and fungi that enhances the uptake of mineral nutrients from the soil and enables the plant to tolerate abiotic and biotic stresses. Although previously reported RNA-seq analyses have identified large numbers of AM-responsive genes in model plants, such as Solanum lycopersicum L., further studies are underway to comprehensively understand the complex interactions between plant roots and AM, especially in terms of the short- and long-term responses after inoculation. Results Herein, we used RNA-seq technology to obtain the transcriptomes of tomato roots inoculated with the fungus Rhizophagus irregularis at 7 and 30 days post inoculation (dpi). Of the 1,019 differentially expressed genes (DEGs) in tomato roots, 635 genes showed differential expressions between mycorrhizal and non-mycorrhizal associations at the two time points. The number of upregulated DEGs far exceeded the number of downregulated ones at 7 dpi, and this difference decreased at 30 dpi. Several notable genes were particularly involved in the plant defense, plant growth and development, ion transport, and biological processes, namely, GABAT, AGP, POD, NQO1, MT4, MTA, and AROGP3. In addition, the Kyoto encyclopedia of genes and genomes pathway enrichment analysis revealed that some of the genes were involved in different pathways, including those of ascorbic acid (AFRR, GME1, and APX), metabolism (CYP, GAPC2, and CAM2), and sterols (CYC1 and HMGR), as well as genes related to cell division and cell cycle (CDKB2 and PCNA). Conclusion These findings provide valuable new data on AM-responsive genes in tomato roots at both short- and long-term postinoculation stages, enabling the deciphering of biological interactions between tomato roots and symbiotic fungi.